Towards linking environmental law and science - Jonathan W. Moore; Linda Nowlan; Martin Olszynski; Aerin L. Jacob; Brett Favaro; Lynda Collins; G.L. Terri-Lynn Wi; Jill Weitz (Canadian Science Publishing, 2018)
Gaps between environmental science and environmental law may undermine sound environmental decision-making. We link perspectives and insights from science and law to highlight opportunities and challenges at the environmental science-law interface. The objectives of this paper are to assist scientists who wish to conduct and communicate science that informs environmental statutes, regulations, and associated operational policies (OPs), and to ensure the environmental lawyers (and others) working to ensure that these statutes, regulations, and OPs are appropriately informed by scientific evidence. We provide a conceptual model of how different kinds of science-based activities can feed into legislative and policy cycles, ranging from actionable science that can inform decision-making windows to retrospective analyses that can inform future regulations. We identify a series of major gaps and barriers that challenge the successful linking of environmental science and law. These include (1) the different time frames for science and law, (2) the different standards of proof for scientific and legal (un)certainty, (3) the need for effective scientific communication, (4) the multijurisdictional (federal, provincial, and Indigenous) nature of environmental law, and (5) the different ethical obligations of law and science. Addressing these challenges calls for bidirectional learning among scientists and lawyers and more intentional collaborations at the law-science interface.